Resiliensi Pembentuk Spirit of Place Komplek Katolik Muntilan. - Rihadiani, Rosalia; Rahmi, Dwita Hadi (RUAS, 2023)
The spirit of place in an area often changes due to natural or human factors. The Muntilan Catholic Complex was founded 1904 as a mission center for native teachers' schools. The architectural styles are village style, Hinduism, Art Deco, and Neo-Gothic. The Catholic complex's architectural form and environment are well preserved, and the functions still remain. This research aims to see the resilience of tangible and intangible heritage in Catholic complexes that form a spirit of place. The research uses qualitative methodology with field observation, literature studies, and interviews to obtain data. The data was then analyzed narratively. The aspects studied were the resilience of architectural, spatial, and visual forms. From an architectural perspective, the infill of the building was carried out due to the replacement of a building that was burnt down (1948). The spatial pattern formed from the building pattern that created the inner courtyard has stayed the same since 1914. The visual architectural style of the new building needs to consider its influence on the spirit of place of the Muntilan Catholic Complex.